Effects of Illegal Solid Waste Dumping on the Structure of Soil Bacterial Communities: A Case Study in China - Jialiang Chen; Lulu Zhang; Lang Song; Mai Ye; Lin Wang; Bin Fan; Bin Li; Zetao Yang; Rongzhou Jin; Pu Jia (Toxics)
Illegal solid waste dumping is a significant factor contributing to environmental damage. In this study, 16S rRNA gene sequencing technology was used for the identification and assessment of environmental damage in an illegal dumping area in China, with the aim of confirming environmental damage through analyzing changes in the soil bacterial communities across slag, sewage sludge, and non-contaminated areas. The results indicate that the diversity of soil bacteria decreases with an increase in the degree of pollution. The illegal dumping of slag resulted in an increase in the relative abundance of Firmicutes and a decrease in the relative abundance of Acidobacteriota. Additionally, illegal dumping of sewage sludge resulted in an increase in the relative abundance of Proteobacteria and a decrease in the relative abundance of Acidobacteriota. The contents of Ni and Be in slag and Cu, Pb, and Cd in sewage sludge were key factors affecting bacterial community composition. The results reveal the effects of heavy metal pollution on the soil bacterial community structure and its environmental driving factors, thus expanding understanding in the context of management of the environmental damage caused by illegal dumping, as well as providing a perspective on the changes in the soil bacterial community, allowing for environmental damage confirmation.